Acquired hemophilia – A pada penderita Waldenstrom’s Macroglobulinemia: laporan kasus - Alamsyah Alamsyah; Herniah Asti Wulanjani (Intisari Sains Medis, 2019)
Background: Acquired hemophilia A (AHA) is a rare acquired bleeding disease, characterized by autoantibody against factor VIII. Bleeding usually in the skin and mucosal. AHA frequently in the elderly, in male and female and is associated with several conditions, such as autoimmune, pregnancy, drug reactions, solid tumor and monoclonal gammopathy. Half of patients are idiopathic. AHA is diagnosed in patients without previous personal or family bleeding history in which prolonged aPTT is not corrected after mixing and accompanied by a decrease in FVIII levels. Specific antibody that plays a role in inhibiting FVIII activity can be seen from the immonotyphing examination. Waldenstrom’s Macroglubulinemia (WM) is a one of disorders that can cause AHA.Case Description: A 56-year-old man came with a weak and pale 10 days of hospitalized. Physical examination shown anemia, gum bleeding, lien palpable in Shuffner-1. Laboratory shown bisitopenia and leukocytosis, prolonged aPTT is not corrected after mixing with decrease FVIII levels. (BMP) support Chronic Lympocytic Leukemia/Lymphoma/ Smoldering Myeloma. SPE M-Spike with Immunotyphing examination of IgM lamda monoclonal. History, physical examination, laboratory, BMP, SPE, and immunotyping shown monoclonal gammophaty which cause Acquired Hemophilia A. Bethesda assay examination recommended if FVIII therapy is not responding. Lymphoplasmasitoid cells infiltration and monoclonal IgM production establishes diagnosis of WM.Conclusion: Spontaneous hemorrhage without prior history with prolonged aPTT is not corrected after mixing and followed by a decrease in FVIII leves can lead to (by the presence inhibitor factors) coagulation disorders.